The morphosedimentary behaviour of a headland–beach system: Quantifying sediment transport using fluorescent tracers - Oliveira, Sónia (2017)
Embayed beaches occurring along rocky coasts with headlands controlling hydrosedimentary processes are considered to be constrained sedimentary systems with little longshore sediment transfer between them. Such beaches are likely to narrow under rising sea level and a deficit of fluvial sediment, and because beaches act to dissipate wave energy, cliff erosion is expected to increase. Knowledge of hydrosedimentary processes in fetch-limited environments such as embayed beaches is therefore a fundamental management tool in erosionprone coastal areas such as the Algarve region (southern Portugal). Themain objective of this work is to quantify longshore sediment transport (LST) using a sedimentary tracer and compare the resultswith the ones derived via empirical formulae from several authors. To achieve this, we establish the spatial and temporal patterns of stained sediment, and relate these to marine climate data over six tidal cycles for three adjacent embayed beaches. The values of displaced sand estimated using tracer and scaled to mixed layer depth were compared with the results of five well-known LST formulae to assess the applicability of eachmodel to mesotidal environments. Of the LST formulae used, the CERC (2013) shows to be the most accurate in our study area. This study demonstrates the efficacy of using tracers for tracking and quantifying the sediment transport and as a basis for assessing the viability of different LST formulae for representing transport in these types of environments. Thework also shows the importance of themorphological control of hydrosedimentary processes, including the disruption of longshore drift and the sediment transfer promoted by shore platforms.